Levinas, law, politics - Diamantides, Marinos (Routledge-Cavendish, 2007)
Emmanuel Levinas re-formulation of subjectivity, responsibility and the good has radically influenced post-structuralist thought. This volume critically engages with an idealisation of Levinas ethics. It also talks about the rebelliousness of Levinas thought and uses it to challenge the preconceptions of social and individual responsibility.